Brand Image and Product Quality as Determinants of Electric Car Purchase Decisions in Depok City - Wisnuaji, Putra Tangguh; Widodo, Djoko Setyo; Udriyah, Udriyah (Klabat Journal of Management, 2026)
This study aims to analyze the influence of Brand Image and Product Quality on the Purchase Decision of Wuling electric cars in Depok City. The research method used was quantitative with a survey approach, and data were collected through questionnaires from 100 respondents who used Wuling electric cars. Data analysis was carried out using multiple linear regression. The results showed that partially, Brand Image did not have a significant effect on purchase decisions, while Product Quality had a significant effect. Simultaneously, the two variables had a significant effect on the purchase decision with an F value of 21.888 and a significance of < 0.001. An Adjusted R Square value of 0.297 indicates that Brand Image and Product Quality explain 29.7% of the variation in purchasing decisions. These findings make a theoretical contribution to the consumer behavior literature, as well as a practical contribution to automotive companies, particularly in the formulation of electric vehicle marketing strategies. The study also suggests strengthening branding strategies, improving product quality, and exploring other external factors such as price, promotion, and after-sales service. The limitations of the study include a limited geographical scope.